Approaches to Inclusive Pedagogy: A Systematic Literature Review - Moriña, Anabel (Pedagogika, 2023)
The paper presents a systematic review of inclusive pedagogy; it differences between inclusive education, inclusive practice, and inclusive pedagogy; the pedagogic approach adopted integrates four elements: beliefs, knowledge, design and actions; further research is needed to determine what teachers do, how, and why they do it.